Evaluation of the "steal" phenomenon on the efficacy of hypoxia activated prodrug TH-302 in pancreatic cancer. - Kate M Bailey; Heather H Cornnell; Arig Ibrahim-Hashim; Jonathan W Wojtkowiak; Charles P Hart; Xiaomeng Zhang; Rafael Leos; Gary V Martinez; Amanda F Baker; Robert J Gillies (PLoS ONE)
Pancreatic ductal adenocarcinomas are desmoplastic and hypoxic, both of which are associated with poor prognosis. Hypoxia-activated prodrugs (HAPs) are specifically activated in hypoxic environments to release cytotoxic or cytostatic effectors. TH-302 is a HAP that is currently being evaluated in a Phase III clinical trial in pancreatic cancer. Using animal models, we show that tumor hypoxia can be exacerbated using a vasodilator, hydralazine, improving TH-302 efficacy. Hydralazine reduces tumor blood flow through the "steal" phenomenon, in which atonal immature tumor vasculature fails to dilate in coordination with normal vasculature. We show that MIA PaCa-2 tumors exhibit a "steal" effect in response to hydralazine, resulting in decreased tumor blood flow and subsequent tumor pH reduction. The effect is not observed in SU.86.86 tumors with mature tumor vasculature, as measured by CD31 and smooth muscle actin (SMA) immunohistochemistry staining. Combination therapy of hydralazine and TH-302 resulted in a reduction in MIA PaCa-2 tumor volume growth after 18 days of treatment. These studies support a combination mechanism of action for TH-302 with a vasodilator that transiently increases tumor hypoxia.